(untitled) (Journal of Engineering and Health Sciences, 2024)
Evans et al. (2023) highlight that pressure ulcers can lead to severe complications, significantly reducing quality of life and even increasing mortality rates among affected individuals. Hence, early prevention and treatment of pressure ulcers, especially in high-risk patients, is crucial. Geriatric patients are particularly vulnerable to developing pressure ulcers due to factors like reduced mobility, skin fragility, and multiple comorbidities. This research aims to assess the effectiveness of frequent repositioning using ripple mattresses in preventing pressure ulcers among elderly patients in medical wards. Specifically, it will compare the efficacy of using ripple mattresses alone versus in combination with other interventions. The study is designed as a prospective interventional trial with the primary goal of evaluating the effectiveness of different strategies to prevent pressure ulcers in immobilized elderly patients. Conducted at General Hospital Melaka, the study will take place in a controlled setting, assessing the impact of preventive measures over a specific period. The success of the intervention is demonstrated by notable improvements in Braden Scale scores and a reduction in pressure ulcer incidence in the group receiving the combined intervention. By adopting evidence-based strategies, healthcare professionals can significantly enhance patient care, reduce the prevalence of pressure ulcers, and improve the quality of life for at-risk elderly patients.